GPS Telemetry Reveals a Zebra With Anthrax as Putative Cause of Death for Three Cheetahs in the Namib Desert - Portas, Ruben; Aschenborn, Ortwin H. K.; Melzheimer, Joerg; Le Roux, Manie; Uiseb, Kenneth Heinrich; Czirják, Gábor Árpád; Wachter, Bettina (Frontiers in Veterinary Science, 2021)
Anthrax is a bacterial disease caused by Bacillus anthracis that affects wildlife, livestock and also humans. It is endemic in some parts of Africa, including Namibia, with species differing in their susceptibility to the disease. Carnivores are typically less susceptible to anthrax than herbivores. Most carnivore species have high seroprevalence against anthrax and survive infection, whereas most herbivore species have low seroprevalence and typically die quickly when infected. Several reports have shown that cheetahs, unlike most other large carnivores, are susceptible to anthrax leading to a sudden death. This finding was suggested to be linked to the low genetic variability of cheetahs which might reduce an adequate immune response and thus explain such a high susceptibility to the disease. Here, we report an incidence of three free-ranging cheetahs that died within 24 hours after feeding on a mountain zebra tested positive for anthrax in the Namib Desert. We were able to reconstruct this incidence with the GPS (Global Positioning System) collar worn by one of the cheetahs and retrieved in the field. It is very likely that the cheetahs died from anthrax, although the bacteria could not be identified in their samples. The mountain zebra is the first described case of a wild animal tested positive for anthrax in this arid area in southern west of Namibia. We discuss the negative laboratory results of the cheetahs in the light of new insights of their immune system and its potential to mount a response against this bacteria.